The child witness : an investigation into children's understanding of the legal process and the perceived competence of children to act as witnesses in legal proceedings - Maunsell, Catherine (Trinity College (Dublin, Ireland). School of Psychology, 2000)
Given recent public and professional concern in relation to the levels of child victimisation and recent reforms of the evidentiary rules and legal procedures pertaining to children's evidence, there is an increasing likelihood that children will appear as witnesses in Irish legal proceedings.
Keywords: Psychology, Ph.D.; Ph.D. Trinity College Dublin